2020
DOI: 10.3389/fmolb.2020.593866
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Citrate Is a Trojan Horse for Cancer Cells

Abstract: The first intermediate in the mitochondrial tricarboxylic acid (TCA) cycle is citrate, which is essential and acts as a metabolic regulator for glycolysis, TCA cycle, gluconeogenesis, and fatty acid synthesis. Within the cytosol, citrate is cleaved by ATP citrate lyase (ACLY) into oxaloacetate (OAA) and acetyl-CoA; OAA can be used for neoglucogenesis or in the TCA cycle, while acetyl-CoA is the precursor of some biosynthetic processes, including the synthesis of fatty acids. Accumulating evidence suggests that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…The rewiring of the metabolic pathway within the mitochondria involves many metabolites, such as citrate, which is the first intermediate in the TCA cycle [ 52 ]. In metabolic reprogramming, increased exportation of citrate from the mitochondria to the cytosol occurs ( Figure 3 B).…”
Section: Mitochondrial Changes and Tca Cycle Rewiringmentioning
confidence: 99%
“…The rewiring of the metabolic pathway within the mitochondria involves many metabolites, such as citrate, which is the first intermediate in the TCA cycle [ 52 ]. In metabolic reprogramming, increased exportation of citrate from the mitochondria to the cytosol occurs ( Figure 3 B).…”
Section: Mitochondrial Changes and Tca Cycle Rewiringmentioning
confidence: 99%
“…Experimental studies showed that physiological concentration of citrate (200 µM) can sustain the proliferation of various cancer cells, such as prostate, pancreatic and gastric ones [ 130 , 131 ]. Interestingly, citrate concentrations of up to 5 mM can stimulate lipid synthesis and histone acetylation in HepG2 cells, but higher concentrations (10 mM or more) decreased both acetylation and ACLY expression [ 132 ]. Factors influencing the blood concentration of citrate (which is normally around 100–150 µM [ 133 ]) have not been well characterized up to now.…”
Section: The Possible Role Of Citrate In the Metabolism Of The Microenvironmentmentioning
confidence: 99%
“…This transporter has been cloned from the citrate releasing prostate secretory epithelial cells ( Mazurek et al, 2010 ) and determined to change citrate transport direction, depending on the cell type in which it is expressed ( Mazurek et al, 2010 ; Mycielska et al, 2018 ). Moreover, extracellular citrate can directly promote cancer proliferation ( Petillo et al, 2020 ) and alter metabolism in vitro ( Mycielska et al, 2018 ). In addition, pmCiC was found to be overexpressed in human cancer cells compared with their benign counterparts in vivo, where it was found to correlate with tumour grade, and was particularly increased at the invasion front and metastatic sites of tumours of different origin ( Mycielska et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%